Forms and regional distribution of knowledge transfer by German universities - Thomas Sauer; Matthias-Wolfgang Stoetzer; Andrea Gerlach (Ernst-Abbe-Fachhochschule Jena, Fachbereich Betriebswirtschaft, 2007)
For the first time the transfer activities of two different German university types - the Friedrich Schiller University (FSU) and the University of Applied Sciences Jena (FH Jena) - were documented in parallel over all departments and channels of technology transfers with regard to their regional significance. Five groups of transfer activities are distinguished in the study: (1) those oriented on human capital, (2) those oriented on classic research and development, (3) those oriented on enterprises, (4) those oriented on direct transfers and (5) informal knowledge transfer channels. The results show that the traditional R&D-activities of the universities for the region are embedded into important supplemental transfer channels. In addition the radii of the external relations of the two universities are complementary: FH Jena has a stronger regional bearing, while FSU is more strongly active supra-regionally and internationally. It is possible that stronger support of the university faculty's activities establishing knowledge transfer could increase the regional economic impact of such activity.
urn:nbn:de:gbv:27-20100929-164030-0
Keywords: O32; R11; I20; 370; innovation systems; technology transfer; regional development; Universities; know-how-transfer